Copy letter from Roger Casement to Gertrude Bannister, raging against the submissiveness of the US towards Britain - Casement, Roger, 1864-1916; Bannister, Gertrude, d. 1950 (1912)
Casement focuses on the willingness of the US Senate to hold an inquiry "into the loss of a British vessel [the Titanic] at sea". Casement admits relief at how "the Putumayo Mission [is] off my shoulders", though he fears that the Titanic disaster will limit public sympathy for some "far off Indians".
Typescript copy with corrections in black ink, addressed from: "Carnstroan, Myrtlefielf [sic] Park, / Belfast".
Keywords: Casement, Roger, -- 1864-1916 -- Correspondence; Bannister, Gertrude, -- d. 1950 -- Correspondence; Titanic (Steamship); Human rights workers; Great Britain -- Foreign relations -- United States; United States -- Foreign relations -- Great Britain